Empathic Attitude of Dental Students from a Peruvian Public University Associated with Reading Habit: a Regression Analysis - Garcia-Rupaya, Carmen R. (2024)
The present study aims to identify the empathic attitude of dental students from a Peruvian public university, about their reading habits, as well as the level of studies and other sociodemographic variables. 226 first-, fourth-, and sixth-year students registered in the academic year 2022 were enrolled in the study. The Jefferson Empathy scale, which included 20 items, was used with a Likert scale ranging from 1 to 7, i.e., from totally disagree to totally agree. A file containing questions about the sociodemographic data registry was prepared together with the Jefferson Empathy questionnaire. It was found that the profile of the students was mainly feminine, and the average age was 22 years; they came from Lima. They had the habit of reading and a little more than half of the group did not participate in sports activities. The "adequate" level of empathy was the highest (51.77%). By dichotomizing the response variable, it was found that adequate empathy was related to the habit of reading, especially reading dental books. Dental students from this public university mostly have an adequate level of empathy; it is independent of the sociodemographic variables but is related to reading habits.